Design and experiment of an air-suction potato seed metering device - Jinqing, Lü; Ying, Yang; Zihui, Li; Qinqin, Shang; Jicheng, Li; Zhongyuan, Liu (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: An air-suction potato seed metering device was designed to improve the performance of the large-size seed crops planting equipment and provide a solution for problems on the mechanical potato seeder, such as high multiple index, high miss index, low qualified index, and limited versatility. The main structure and operation parameters in terms of rotating speed of the device, seeds height and pickup vacuum pressure were determined by theoretical analysis. Two orthogonal tests, conventional tuber (the triaxial average diameter is about 38-57 mm) test and mini-tuber (the triaxial average diameter is about 12-36 mm) test, were conducted to analyze the influences of these factors on the quality of seeding. The multiple index, miss index and qualified index were chosen for evaluating the working performance. The results of conventional tuber test showed that, the multiple index was 1.1%, the miss index was 0.8% and the qualified index was 98.1% under conditions of the 30 r/min rotating speed, 25 cm seeds height and 10 kPa pickup vacuum pressure. The results of mini-tuber test showed that the multiple index was 0.5%, the miss index was 0.6% and the qualified index was 98.9% under conditions of 35 r/min rotating speed , 17 cm seeds height and 3.5 kPa pickup vacuum,. The working performances of the device can meet the requirements of precision seeding. Keywords: air-suction, seed metering device, mini-tuber, precision seeding, potato, pickup vacuum DOI: 10.3965/j.ijabe.20160905.2221 Citation: Lü J Q, Yang Y, Li Z H, Shang Q Q, Li J C, Liu Z Y. Design and experiment of an air-suction potato seed metering device. Int J Agric & Biol Eng, 2016; 9(5): 33-42.